Hydrothermal Synthesis of Iodine-Doped Nanoplates with Enhanced Visible and Ultraviolet-Induced Photocatalytic Activities - Jiang Zhang; Zheng-Hong Huang; Yong Xu; Feiyu Kang (International Journal of Photoenergy)
The iodine-doped Bi2WO6 (I-BWO) photocatalyst was prepared via a hydrothermal method using potassium iodide as the source of iodine. The samples were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM) and selected area electron diffraction (SAED), X-ray photoelectron spectroscopy (XPS), UV-vis diffuse reflectance spectroscopy (DRS), and photoluminescence (PL) spectroscopy. The photocatalytic activity of I-BWO for the degradation of rhodamine B (RhB) was higher than that of pure BWO and I2-BWO regardless of visible light (>420 nm) or ultraviolet light (<400 nm) irradiation. The results of DRS analysis showed that the I-BWO and I2-BWO catalysts had narrower band gaps. XPS analysis proved that the multivalent iodine species including I0 and were coadsorbed on the defect surface of Bi2WO6 in I-BWO. The enhanced PL intensity revealed that a large number of defects of oxygen vacancies were formed by the doping of iodine. The enhanced photocatalytic activity of I-BWO for degradation of RhB was caused by the synergetic effect of a small crystalline size, a narrow band gap, and plenty of oxygen vacancies.